Gene expression profiling demonstrates differential expression of osteopontin in follicular thyroid carcinomas compared to normal thyroid tissue in dogs. (25th August 2012) - Metivier, K. S.; Deitz, K.; Xu, W. W.; Conzemius, M.; Wilke, V. L.
Abstract Follicular thyroid carcinoma (FTC) is an aggressive tumour in dogs with little known about its molecular pathogenesis. The overall goal of this study was to examine FTC and normal thyroid tissue gene expression. Microarray analysis was performed on a pilot group of five FTC‐affected dogs and four healthy dogs, and then osteopontin validated with quantitative polymerase chain reaction (PCR) and immunohistochemistry (IHC) of thyroid tissue from non‐invasive FTC, invasive FTC and healthy dogs. On microarray analysis, 489 transcripts were differentially expressed between FTC and normal thyroid: 242 transcripts were down‐regulated and 247 were up‐regulated. Osteopontin expression was markedly increased in tumour tissue compared to normal thyroid tissue. Quantitative PCR and IHC confirmed differential expression of osteopontin in both tumour types (invasive and non‐invasive) compared to normal thyroid tissue. There is justification for further investigation of osteopontin as a potential molecular marker for screening and monitoring of canine FTC.